Geometry of fiber distribution in Marl yarn using the computational method. Issue 4 (3rd April 2019) - Moezzi, Meysam; Ghane, Mohammad
Abstract: In this research, the structure of a type of bi-component composite yarns so called Marl yarn was studied. Fibers packing density factors within the yarn cross section as well as the effect of twisting on the resultant yarn were investigated. Samples of Marl acrylic yarns were provided using different twisting levels. Images of the cross sections of the produced yarn were obtained using the transverse sectioning method. The images were captured using the optical microscopy. The prepared images of the yarn cross section were then analyzed using image processing methods. In the first stage, yarn central coordinates and radiuses were calculated. In order to investigate the uniformity of fibers distribution and packing density within the yarn cross section, the fiber distances from the yarn center within the small radial and polar elements were calculated and the coefficient of variations (CV %) was determined. The maximum value of the fibers packing density was determined. The results showed that the fibers were mostly concentrated within the central region of the yarn; this was followed by the decrease in the fibers packing density while moving into the yarn's outer layers. It was also concluded that increasing the intensity of the applied twist would result in higher fibers packing as well as the decrease in the yarn radius.